Differentiation of body fat composition between skinfold caliper (SKF) and bioelectrical impedance analysis (BIA) methods among professors - Nicole Ngo Zhe Yiin; Leonardo Lubis; Dimas Erlangga Luftimas (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2018)
Body fat composition reflected by body fat percentage (BF%) is one of the important components in disease risk evaluation. Among the methods available to measure BF%, skinfold calipers (SKF) and bioelectrical impedance analysis (BIA) are the most commonly used. The study was conducted to evaluate the difference in body fat composition measurement between SKF and BIA methods among professors. This study analyzed secondary data from the health evaluation of Universitas Padjadjaran (UNPAD) professors. This study involved 72 professors (50 male, 22 female) after fitted into the inclusion and exclusion criteria. BF% was measured among UNPAD professors using SKF and BIA. After obtaining agreement by Bland-Altman Plot, the data were analyzed by muliple paired-t test according to gender, physical activity level and body mass index (BMI) categories. The study showed no significant difference in BF% between SKF and BIA in overall population, between gender and physical activity level (p>0.05). For BMI, the only category that showed significant difference in BF% between the 2 methods was obese I group (p=0.001). In conclusion, there is no significant difference in BF% between SKF and BIA methods according to gender, physical activity levels and BMI categories except for obese I group.